Coffee Tradition - Suheri, Suheri (Proceedings of Annual Conference for Muslim Scholars, 2025)
This research explores the evolution of the coffee-drinking tradition from a private familial practice to a global medium for cross-cultural communication and social facilitation. Positioned as a symbolic bridge for cultural diplomacy, coffee is analyzed not merely as a commodity but as an egalitarian instrument for conflict resolution and trust-building. Adopting a constructivist paradigm with a qualitative approach, the study utilizes participant observation, in-depth interviews with cultural practitioners, and the Miles and Huberman interactive model for data analysis. The findings reveal that coffee serves as a "cultural text" that facilitates persuasive, relational, and problem-solving dialogues across diverse religious and national boundaries. The study offers two significant theoretical contributions: first, the Global Coffee Harmony Theory (GCHT), which frames coffee as a model for informal cultural diplomacy; and second, "Harmony Through Symbolic Communication," which conceptualizes the act of drinking coffee as a preventive and curative tool for fostering global solidarity. Ultimately, the research concludes that coffee-based interactions provide a robust framework for creating tolerance and sustainable social harmony in a globalized society.